Long-Term Effects of Tai Chi Intervention on Sleep and Mental Health of Female Individuals With Dependence on Amphetamine-Type Stimulants - Zhu, Dong; Dai, Guobin; Xu, Ding; Xu, Xin; Geng, Jingjing; Zhu, Weimo; Jiang, Xi; Theeboom, Marc (Frontiers in Psychology, 2018)
Previous studies provide evidence that Tai Chi (TC) can reduce the symptoms of sleep problems and be of benefit for the rehabilitation of substance abusers. In this study, we investigated if TC practice can improve sleep quality and mood of females who are dependent on amphetamine-type stimulant (ATS). Eighty subjects were randomly assigned to TC intervention and standard care (SC) for 6 months. We applied analysis of variance on repeated-measure with the year of drug dependence as the covariate to test the changes of the self-rated Pittsburg Sleep Quality Index (PSQI), Self-Rating Depression Scale (SDS), as well as fitness after 3 and 6 months. Relapse investigation was conducted by checking the database of China's National Surveillance System on Drug Abuse and that of the Shanghai Drug Control Committee's illicit drug dependents. Our investigation focused on the relapse of participants who had undergone and completed treatment in the Shanghai Mandatory Detoxification and Rehabilitation Center in 2015. The result showed that the PSQI scores of sleep duration [F(2, 92) = 9.86], need for sleep medications [F(2, 92) = 36.44] and daytime dysfunction [F(2, 92) = 5.15] were found to have a significant difference by time × group interaction after 6 months. SDS showed no significant difference between the two groups; however, the score of SDS in TC decreased after 6-month intervention, and no changes were observed in SC. Pulse rate had significantly decreased in the TC group compared with the SC group after 6 months. 9.5% (4) ATS dependents in TC and 26.3% (10) ATS dependents in SC were found to have relapsed. Our result suggested that TC had positive effects on sleep quality, depression and fitness. Long-term study demonstrated that TC may be a cheap and potential supplementary treatment for ATS-dependent individuals. TC may also be considered as an alternative exercise to escalate abstinence for ATS-dependent females. Clinical trial registration: ChiCTR-IPR-14005343 chictr. org.cn